Mobile application tool for remote rehabilitation after discharge from coronavirus disease‐19 rehabilitation unit. Issue 4 (8th August 2022) - Emedoli, Daniele; Alemanno, Federica; Houdayer, Elise; Brugliera, Luigia; Iannaccone, Sandro; Tettamanti, Andrea
Abstract: A smartphone application (Medico‐Amico) has been developed by the collaboration of San Raffaele Scientific Institute and Khymeia Group S.R.L. with the aim of providing physical exercises and communicating with patients after their hospitalization in a coronavirus disease (COVID)‐rehabilitation unit. Thirty patients used the application for remote rehabilitation for 4 weeks. They were prescribed personalized motor exercises to perform three times a week. Clinicians could interact with each patient by an encrypted video call in order to give encouragement, mental support, modify intensity during training sessions, or to prescribe new exercises. Patients were asked to perform motor exercises and also to monitor their vital signs, such as temperature, blood pressure, and oxygen saturation, inserting scores in a specific section of the application. After 4 weeks of remote rehabilitation patients showed improvements in independence during activity of daily living and strength. Also, satisfaction and mobile application usability scores reached patients' appreciation and enjoyment.